DESIGN CRITERIA OF SOIL-FIBER MIXTURES AS A MATERIAL FOR LANDFILL COVER BARRIER SYSTEM - Tri Harianto (Lowland Technology International, 2014)
The design criteria were introduced in this paper to design a landfill cover barrier layer using the compacted soil-fiber mixture for the future application (i.e. park, residential, etc.). Polypropylene (C3H6) fiber was used as an additive material for soil samples. The soil specimens compacted under the conditions of maximum dry density and optimum water content. In this study, the design objective in using the compacted soil-fiber mixture is to determine the range of fiber content (i.e. 0.0% - 1.2%) within which the soil specimens will have adequate compaction characteristics, compressive and tensile strength, minimum amount of cracking, and low hydraulic conductivity. It is found that the fiber content that maximized the maximum dry density was considered insignificant. Fiber content in excess of 0.8% showed significant increase in the unconfined compressive strength. The tensile strength significantly increased for soil specimens exceeding 0.2% of fiber content. An acceptable limiting value of the crack intensity factor to prevent desiccation cracking for soil specimen was found between 0.6 and 0.8% of fiber content. Moreover, the fiber contents up to 1.2% maintained the hydraulic conductivity within acceptable levels. As a result, the optimum fiber content that was necessary to meet the overall acceptable zones based on the parameter design investigated in this study was found and reported in this study.